Fermentation, Isolation, Purification and Biological Activity of SJA-95, a Heptaene Polyene Macrolide Antibiotic Produced by the Streptomyces sp. Strain S24 - Naik, Suresh R.; Desai, Sandhya K.; Nanda, Rabindra K.; Narayanan, Mangalam S. (Arzneimittelforschung, 2007)
A new strain, Streptomyces sp. S24 was isolated from a soil sample collected from Japan. Preliminary morphological, cultural, physiological and biochemical studies on this strain were carried out. Under submerged culture conditions the strain produced heptaene polyene macrolide (SJA-95), which elicits promising antifungal activity in vitro against yeasts, filamentous fungi including clinical isolates and plant pathogens. Its antifungal activity is comparable to that of hamycin and amphotericin B. SJA-95 was found to be toxic when given by the parenteral route in mice and not absorbed by the oral route like other polyene heptaene macrolides.The physicochemical data, spectral studies and elemental analysis suggest that SJA-95 is a polyene macrolide antibiotic. However, the chemical structure needs to be elucidated by further spectroscopic studies viz. 13C NMR, FEB-MS, EL MS and other tests.
Keywords: Antibiotic, polyene macrolide; Antifungal; Heptaene polyene macrolide; SJA-9, acute toxicity, antifungal activity, physicochemical property; Streptomyces sp. S24, fermentation